Nigeria : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This report provides the IMF's projections and estimates on Nigeria's gross domestic product by sector of origin at current domestic prices and constant 1990 prices; by expenditure category at current prices and constant 1990 prices; consolidated government finances, revenue, and expenditure; federation account operations; summary federal government fiscal operations; budgeted total, recurrent, and capital expenditures of the federal government by functional classification; monetary survey; balance of payments; consolidated accounts of the central bank, commercial, and merchant banks, during 1993-98; summary of the tax system as of June 1999, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet